(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
The article is devoted to the problem of combining traditional and modern innovative pedagogical technologies (on the example of the training of geological engineers at the North-Eastern State University). It is shown that the success of the educational process depends on the correct combination of modern and traditional teaching methods.